A Scheme for Partial Enumerations in the Hills - Seth, S. K. (Indian Forester, 1951)
Orthodox sampling methods used in Forestry depend upon accurate survey to locate and demarcate the sampling units. This item is chiefly responsible for the disproportionately large amount of time and money required for partial sampling as compared to total enumerations over whole compartments. A method is described which dispenses with survey almost altogether as it makes use of the detail given in large scale survey maps both to locate the sampling units on the ground and to determine their areas accurately. Its chief utility lies for sampling in the hills because it is possible to mark out comparatively small (30-75 acres) sampling units on survey maps. Stratifkd sampling with enumeration of two sampling units per block is advocated and the expression for calculating the fiduciary limit of the mean growing stock per acre is given. The question of weightage to allow for differences in areas of sampling units is discussed.